Formation of Land Holdings of Murzas Kulmametevy and Seydyashevy in 17th Century - G. K. Samigulov; Z. A. Tychinskikh (Научный диалог)
The issue of land ownership in the aboriginal population of Western Siberia in the 17th century is examined. Special attention is paid to the formation of large estates of serving Tatars Kulmametevy and, to a lesser extent, Seydyashevy, who were the second “branch” of the same family. Variants for land acquisition are described: by purchase, awards, compensation, seizures, etc. The results of archival research and material processing are presented. The proposed material is a publication of sources with the required review and preliminary conclusions. Complex of archival materials is introduced in the scientific usage, that shows the process and extent of land acquisition by murzas Kulmametevy and Seydyashevy. Scientific novelty of the research lies in the fact that: (1) most of the materials are published for the first time; (2) the example of a particular family of serving Tatars shows the complex processes of the formation of the land policy of the Russian state in the newly acquired territories of Siberia in the 17th century; (3) majority of cited documents are extracts from census books of Lev Poskochin relating to “Tatar” population of the Siberian districts. It is noted that these books today are not founded.